2015 International Conference on Computing, Networking and Communications (ICNC) 2015
DOI: 10.1109/iccnc.2015.7069441
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid model to extend vehicular intercommunication V2V through D2D architecture

Abstract: Abstract-In the recent years, many solutions for Vehicle to Vehicle (V2V) communication were proposed to overcome failure problems (also known as 'dead-ends'). This paper proposes a novel framework for V2V failure recovery using Device-to-Device (D2D) communications. Based on the unified Intelligent Transportation Systems (ITS) architecture, LTE-based D2D mechanisms can improve V2V 'dead-ends' failure recovery delays. This new paradigm of hybrid V2V-D2D communications overcomes the limitations of traditional V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Finally, as an alternative solution to using IRS at all, different approaches propose vehicle to vehicle routing or device to device relaying. A comparative study of such adhoc non centralized solutions can be found in [17] and [18]. Decision Neural Network (DNN), adhoc or D2D solution stems from the lack of cellular operators willing to deploy additional base stations, however IRS based DNN suffers much less delay than adhoc or D2D due to the necessity to add a large amount of signalling for both concurrent solutions to work correctly (communication delay that will result from all the necessary routing and discovery procedures).…”
Section: Related Workmentioning
confidence: 99%
“…Finally, as an alternative solution to using IRS at all, different approaches propose vehicle to vehicle routing or device to device relaying. A comparative study of such adhoc non centralized solutions can be found in [17] and [18]. Decision Neural Network (DNN), adhoc or D2D solution stems from the lack of cellular operators willing to deploy additional base stations, however IRS based DNN suffers much less delay than adhoc or D2D due to the necessity to add a large amount of signalling for both concurrent solutions to work correctly (communication delay that will result from all the necessary routing and discovery procedures).…”
Section: Related Workmentioning
confidence: 99%
“…The work of [10] studied the effect of the use of drones in the 5G cellular network in terms of capacity, quality, robustness, and correlation stability between the used drones and the ground station. In [11] proposed the use of D2D to alleviate the failure of vehicular communication.…”
Section: Related Workmentioning
confidence: 99%
“…LTE D2D is a promising technology for these hybrid approaches, allowing vertical handovers from DSRC networks to infrastructureless, ad-hoc networks of LTE-enabled vehicles to address network "dead ends" [69]. LTE D2D improves upon DSRC-and cellular-only approaches by facilitating highthroughput, low-latency, communications with minimum spectrum allocation and power consumption [70].…”
Section: Intervehicle Networkmentioning
confidence: 99%